Effects of psychodrama and cognitive behavioral therapy on assertiveness skills of women with marital conflicts - Mahin Tahvilian; Elham Foroozandeh; Seyed Mostafa Banitaba (Journal of Multidisciplinary Care, 2023)
Background and aims: A lack of assertiveness can worsen marital conflicts and cause psychological symptoms. The present study aimed to investigate the effects of psychodrama and cognitive behavioral therapy (CBT) on the assertiveness skills of women with marital conflicts. Methods: This quasi-experimental study was conducted on all married women with marital conflicts visiting the counseling departments of cultural centers at the Municipality of Isfahan (Iran) in 2021. Cluster sampling was employed to select 60 women, who were then assigned to three 20-member groups called CBT, psychodrama, and control using a simple random method. The participants completed the Assertion Inventory before and after the intervention and 60 days after the post-test. The repeated measures ANOVA via SPSS-22 was then used for data analysis. Results: The mean (±SD) of the post-test score of assertiveness skills in the psychodrama and CBT groups was 123.40 (±23.83) and 111.25 (±22.77), respectively, which was different from the control group (83.20 (±21.24)). According to the results, CBT and psychodrama affected the assertiveness components of women with marital conflicts instead of control cases (P<0.001). Furthermore, there were no significant differences between CBT and psychodrama regarding effects on women’s assertiveness components. Conclusion: Considering the positive effects of CBT and psychodrama on improving assertiveness, it is recommended that counseling and psychotherapy centers help women with marital conflict improve their assertiveness skills by providing suitable conditions for conducting CBT and psychodrama sessions.